2021
DOI: 10.1186/s12920-021-01115-6
|View full text |Cite
|
Sign up to set email alerts
|

Gene biomarker prediction in glioma by integrating scRNA-seq data and gene regulatory network

Abstract: Background Although great efforts have been made to study the occurrence and development of glioma, the molecular mechanisms of glioma are still unclear. Single-cell sequencing technology provides a new perspective for researchers to explore the pathogens of tumors to further help make treatment and prognosis decisions for patients with tumors. Methods In this study, we proposed an algorithm framework to explore the molecular mechanisms of glioma b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The counts data from each dataset was used to reassign cell types using scSorter 41 with the following markers used to identify Neoplastic (e.g. NDUFS5, NDUFA1, NDUFA13, NDUFB8 42 , CEND1, DCHS1, TPP1, GATD1, RNH1, SMCR8, SMPD1, CD151 43 , "PTPRZ1", "OLIG2", "PDGFRA", "DLL3", "AQP4", "CLU" 44 ), Proliferating Tumor Cells ("MKI67" 44 ), Oligodendrocytes ("MBP", "TF", "PLP1", "MAG", "MOG", "CLDN11" 45 , "PLP1", "MOG", "SOX10", "MBP" 36,46 ), Astrocytes ('S100B', 'GFAP', "SLC1A3", "GLAST", "MLC1" 45 , "GFAP", "ALDH1L1", "SOX9", "AQP4" 36,46 ), Macrophages ("CD14", "AIF1", "FCER1G", "FCGR3A", "TYROBP", "CSF1R" 45 , "C1QA", "CX3CR1", "CCL3", "TNF" 36,46 , Endothelial (), Neuron ("VGLUT1", "STMN2", "SYT1", "SYN1" 36,46 ), Neural progenitor cells (e.g. "SOX4", "SOX11", "DCX" 45 ,), T-Cillium ("IGFBPL1", "HYDIN" 44 ), T-Cells ("CD2", "CD3D", "CD3E", "CD3G" 45 ,), and Non-identified Immune Cells ("PTPRC", "CD3E", "P2RY12", "CD163", "CXCL1", "FCGR3B", "FCN1" 44 ), and Endothelial Cells ("CLDN5", "ELTD1", "ITM2A", "ESAM" 36,46 ).…”
Section: Single Cell Sequencing Analysis Using Merged Dataset Librarymentioning
confidence: 99%
“…The counts data from each dataset was used to reassign cell types using scSorter 41 with the following markers used to identify Neoplastic (e.g. NDUFS5, NDUFA1, NDUFA13, NDUFB8 42 , CEND1, DCHS1, TPP1, GATD1, RNH1, SMCR8, SMPD1, CD151 43 , "PTPRZ1", "OLIG2", "PDGFRA", "DLL3", "AQP4", "CLU" 44 ), Proliferating Tumor Cells ("MKI67" 44 ), Oligodendrocytes ("MBP", "TF", "PLP1", "MAG", "MOG", "CLDN11" 45 , "PLP1", "MOG", "SOX10", "MBP" 36,46 ), Astrocytes ('S100B', 'GFAP', "SLC1A3", "GLAST", "MLC1" 45 , "GFAP", "ALDH1L1", "SOX9", "AQP4" 36,46 ), Macrophages ("CD14", "AIF1", "FCER1G", "FCGR3A", "TYROBP", "CSF1R" 45 , "C1QA", "CX3CR1", "CCL3", "TNF" 36,46 , Endothelial (), Neuron ("VGLUT1", "STMN2", "SYT1", "SYN1" 36,46 ), Neural progenitor cells (e.g. "SOX4", "SOX11", "DCX" 45 ,), T-Cillium ("IGFBPL1", "HYDIN" 44 ), T-Cells ("CD2", "CD3D", "CD3E", "CD3G" 45 ,), and Non-identified Immune Cells ("PTPRC", "CD3E", "P2RY12", "CD163", "CXCL1", "FCGR3B", "FCN1" 44 ), and Endothelial Cells ("CLDN5", "ELTD1", "ITM2A", "ESAM" 36,46 ).…”
Section: Single Cell Sequencing Analysis Using Merged Dataset Librarymentioning
confidence: 99%
“…Schaum et al [24] performed the CIBERSORTx deconvolution algorithm on annotated scRNA-seq to quantify the abundance of immune cells in 17 organs at ten ages based on their massive bulk RNA seq data which confirmed her findings with scRNA-seq. Recent studies reported applying scRNA-seq and bulk RNA seq data to analyze the tumor heterogeneity and immune cells in ovarian cancer [25], glioma [26], and esophageal squamous cell carcinoma [27]. Jerby-Arnon et al [28] identified a cancer cell-related T resistance program to predict the immunotherapy response in melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Single-cell RNA sequencing (scRNA-seq) is the amplification and sequencing of the transcriptome at the single-cell level [ 9 ], which provides an effective method for studying the cellular heterogeneity of the brain and illuminates the complex mechanisms of the normal physiological or pathological development process [ 10 ]. At present, scRNA-seq is widely used in the research of neurological diseases, such as AD [ 11 ], brain aging [ 12 ], and glioma [ 13 ]. At the same time, the cellular and biochemical components of blood play a central role in human physiology, and their dynamic levels are thought to correlate with the individual’s health and disease states [ 14 ].…”
Section: Introductionmentioning
confidence: 99%